WTO's Special and Differentiated Treatment (S&DT) Principle and Solutions of the US-China Conflict. Issue 4 (31st December 2021) - Hong, Kyoungseo; Yoo, Jeong Ho; Cheong, Inkyo
Abstract : As the US-China conflict intensifies, the United States is pursuing a 'decoupling' strategy to build a new world trade order, arguing that the current World Trade Organization (WTO) system does not properly regulate China's non-market economic system. The WTO provides special and differentiated treatment (S&DT) for developing countries. The United States argues that China should give up its developing country (DC) status. Sufficient research on the DC status and S&DT has not been conducted as a means of resolving the US-China conflict. Decoupling means the collapse of the global supply chain (GSC), which will bring substantial shock to the global economy and a catastrophe for China. This paper examines the re-classification of DC status and S&DT in the context of US-China conflict and seeks an approach for China to avoid decoupling and coexist with the United States. It would be an optimal way for China to revive the WTO first and to improve its economic system through negotiations under the WTO.